TECHNIQUES AND QUALITY OF 'CIVIL WAR: WHOSE SIDE ARE YOU ON?' COMIC TRANSLATION - Rifqi Hanif Barezzi; MR Nababan; Riyadi Santosa (UIN Raden Mas Said Surakarta, 2018)
The objectives of this study were to know the translation techniques and the assessment translation quality of Marvel comic series entitled Civil War: Whose Side Are You? (Part 1 and 2) in terms of accuracy, acceptability, and readability. This was a descriptive qualitative research and focusing on a single case as well as holistic research involving documents, i.e: the original and the translation books as the objective data and informants who gave assesment on the quality of the translation. The techniques of collecting data were document analysis, questionnaire distribution, and focus grup discussion. Total sampling was applied in this research. The research findings show that there were 12 types of translation techniques applied by the translator, namely established equivalent, borrowing, variation, modulation, explication, discursive creation, literal translation, reduction, transposition, addition, adaptation, and implication. The impact of the application of those techniques toward the translation quality was good enough. The scores indicate that the translation has good quality in terms of accuracy, acceptability, and readability. It also shows that background of the translators influenced the techniques chosen.